Sacra virginitas on the Example of St Agnes the Roman in the Light of Selected Early Christian Sources (4th–5th Century) - Piechocka-Kłos, Maria (Studia Warmińskie, 2024)
The aim of this publication is to present the figure of St Agnes in the context of an analysis of the issue of sacra virginitas in selected early Christian sources. In the study, the timeframe of the source research refers to works written in the fourth and fifth centuries. The first part analyses two tests from among the great ecclesiastical writers, while the second part analyses two texts from the field of Christian poetry in the style of classical poetry. First, reference was made to the rhetorical text of St Ambrose De virginibus and Letter 130. To Demetriades (On the Preservation of Virginity) written by St Jerome. The epigram of Pope Damasus and Hymn XIV from Liber Peristephanon by Prudentius were then analysed. A concise study of historical biographical data, supplemented by legendary threads preserved in the traditional accounts of St Agnes, will help to present more fully the issue under study. This study is certainly an interesting addition to the research on the figure of St Agnes and the concept of sacra virginitas.